2015
DOI: 10.1007/s00134-015-3894-y
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal candidiasis: it’s still a long way to get unquestionable data

Abstract: Intra-abdominal candidiasis (IAC) appears as the second most frequent cause of invasive fungal infection in the intensive-care unit (ICU) [1]. In the AmarCand 1 study, a prospective, multicenter, French observational study, IAC was observed in 34 % of ICU patients with proven invasive candidiasis [1]. Intra-abdominal candidiasis accounts for more than 10 % of all cases of peritonitis and is associated with mortality rates between 25 and 60 % [2,3].Intra-abdominal candidiasis shares many similarities with candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Epidemiologic reports, antifungal treatment trials and diagnostic studies of invasive candidiasis have focused largely on candidemia [ 4 ]. Research on IAC is limited by the disease’s clinical heterogeneity, a lack of standardized disease definitions, and difficulties in establishing diagnoses [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic reports, antifungal treatment trials and diagnostic studies of invasive candidiasis have focused largely on candidemia [ 4 ]. Research on IAC is limited by the disease’s clinical heterogeneity, a lack of standardized disease definitions, and difficulties in establishing diagnoses [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…IAC encompasses a range of disease manifestations, which occur in patients with various underlying conditions and risk factors involving the gastrointestinal (GI) tract and digestive system [ 6 , 7 ]. The clinical significance of Candida in cultures of samples from intra-abdominal sites is controversial, as mixed infections with bacteria are frequent and the settings in which antifungal treatment is beneficial are not established conclusively [ 6 , 8 ]. Clearly, Candida contributes to poor outcomes in some patients with intra-abdominal infections [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…in cultures of samples from intra-abdominal sites is controversial and blood cultures are often negative. There are limited data on the utility of using surrogate markers (42,43). Because of diagnostic dificulties, empiric antifungal therapy should be considered for patients with clinical evidence of intraabdominal infection and signiicant risk factors for candidiasis, including recent abdominal surgery, anastomotic leaks, or necrotizing pancreatitis (49).…”
Section: Intra-abdominal Candidiasismentioning
confidence: 99%
“…According to the epidemiological data over the last decades, the mortality rate of patients with IAC was about 25-40%; for those combined with septic shock, the mortality rate was up to 60% [4][5][6]. Unfortunately, IAC remains poorly understood when compared with candidemia [7][8][9]. Previous studies showed that, for patients with candidemia, early antifungal therapy and timely source control improve survival [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%